Novel lignin as natural‐biodegradable binder for various sectors—A review. Issue 15 (6th December 2021) - Mili, Medha; Hashmi, Sayed Azhar Rasheed; Ather, Madeeha; Hada, Vaishnavi; Markandeya, Nishant; Kamble, Sanjay; Mohapatra, Mamata; Rathore, Sanjai Kumar Singh; Srivastava, Avanish Kumar; Verma, Sarika
Abstract: Lignin functions as an essential polymer in plants that forms the plant body's structural framework. The natural glue holds the cellulosic fibers together in the plant body, thereby providing rigidity and strength. Despite this, lignin shows promising relevance for biomaterial production due to its abundance, nontoxic nature and biodegradability. Considerably, adhesive components were derived from petroleum, which is increasingly more expensive. Hence, lignin, the natural glue in plant materials, gained much popularity because of its phenolic nature, making it an attractive substitute for adhesives. Lignin‐based binders are produced through phenols substitution in phenol‐formaldehyde resins with lignin due to their similar structural framework. Many researchers have confirmed the multifunctional applications of lignin, such as wood adhesive in fiber board, plywood and particleboard, a binder in printed wiring boards, abrasive tools, epoxy asphalts, epoxy wood composites, 3D printing, adhesive hydrogels, soil suppressants, lignocellulosic paper and coatings. This review presents a comprehensive description of the utilization of lignin‐based binders for different applications. The present work highlights the discussion on the various methods by which lignin can be used to replace synthetic binders. This review focuses on global research work introducing lignin in different chemical adhesives for a more cost‐effective and less harmful alternative. Abstract :